Potential use of cotton dust as filler in the production of thermoplastic composites - Ayrilmis, Nadir; Güleç, Türker; Peşman, Emrah; Kaymakci, Alperen (SAGE Publications, 2017)
The effect of cotton dust as filler on the mechanical and thermal properties of polypropylene composites was investigated and the results were compared with the properties of wood plastic composites. Cotton dust was obtained from the dust filtration system located in a textile manufacturing unit. Different mixtures of cotton dust (30 to 60 wt%) or wood flour (30 to 60 wt%) were compounded with polypropylene with a coupling agent (maleic anhydride grafted polypropylene 3 wt%) in a twin-screw co-rotating extruder. The test specimens were produced by injection molding machine. The tensile strength and flexural modulus of the specimens improved with the increase in the filler content. There was no significant difference in the strength and modulus values between the cotton dust and wood flour filled composites. The highest thermal stability was found to be in the composites produced with 40 wt% of cotton dust according to the results of differential scanning calorimetry analysis. Based on the findings obtained from the present study, the optimum mechanical and thermal properties for the filled polypropylene composites were found to be a 50/50/3 formulation of cotton dust, polypropylene, and maleic anhydride grafted polypropylene, respectively.
Keywords: 2. Zero hunger